2011
DOI: 10.1016/j.juro.2011.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric 3T Prostate Magnetic Resonance Imaging to Detect Cancer: Histopathological Correlation Using Prostatectomy Specimens Processed in Customized Magnetic Resonance Imaging Based Molds

Abstract: Purpose To determine the prostate cancer detection rate of multi-parametric (MP) MRI at 3T. Precise one to one histopathologic correlation with MRI was possible using prostate MRI based custom-printed specimen molds following radical prostatectomy. Materials and methods This IRB approved prospective study included forty-five patients (mean age 60.2 years, range 49–75 years) with a mean PSA of 6.37ng/mL (range 2.3–23.7ng/mL), who had biopsy proven prostate cancer (mean Gleason score of 6.7; range 6 to 9). Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
321
1
11

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 431 publications
(340 citation statements)
references
References 20 publications
7
321
1
11
Order By: Relevance
“…Indeed, even extended biopsy protocols can miss cancers with unfavorable features, leading to improper selection for AS (17). Multiparametric magnetic resonance (MR) imaging, including both anatomic and functional sequences, has been shown to be effective for the detection and local staging of prostate cancer (18); however, multiparametric MR imaging currently is not included in the decision-making algorithms or criteria for AS. The purpose of this study was to determine whether multiparametric MR imaging can help identify patients who would most appropriately be candidates for AS according to current guidelines and to compare the results with those of conventional clinical assessment scoring systems, including the D'Amico, Epstein, and Cancer of the Prostate Risk Assessment (CAPRA) systems, on the basis of findings at prostatectomy.…”
Section: Genitourinary Imaging: Multiparametric Mr Imaging For Assignmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, even extended biopsy protocols can miss cancers with unfavorable features, leading to improper selection for AS (17). Multiparametric magnetic resonance (MR) imaging, including both anatomic and functional sequences, has been shown to be effective for the detection and local staging of prostate cancer (18); however, multiparametric MR imaging currently is not included in the decision-making algorithms or criteria for AS. The purpose of this study was to determine whether multiparametric MR imaging can help identify patients who would most appropriately be candidates for AS according to current guidelines and to compare the results with those of conventional clinical assessment scoring systems, including the D'Amico, Epstein, and Cancer of the Prostate Risk Assessment (CAPRA) systems, on the basis of findings at prostatectomy.…”
Section: Genitourinary Imaging: Multiparametric Mr Imaging For Assignmentioning
confidence: 99%
“…An imaging score was assigned to each lesion on the basis of its features on images obtained with different pulse sequences at MR imaging, yielding low, moderate, and high suspicion levels (Table 3). For multiparametric MR imaging analysis, on T2-weighted MR images and apparent diffusion coefficient maps from DW MR imaging, the criterion for a "visible" lesion was a well circumscribed, round-ellipsoid, low-signal-intensity region within the prostate gland (18,19). The analysis of three-dimensional MR spectroscopy images evaluated choline (Cho)/citrate (Cit) ratios within voxels in the biopsy core sites.…”
Section: Multiparametric Mr Imagingmentioning
confidence: 99%
“…MR spectroscopy was not performed because of its cost, extra imaging time, and relatively poor sensitivity. 9 Men who had suspicious lesion(s) on MP-MRI and were referred by their primary urologists for study evaluation were then consented and enrolled onto the trial. Exclusion criteria for these analyses included a previous history of CaP, radiation to the pelvis, and inability to tolerate prostate biopsy under local anesthesia or mild sedation.…”
Section: Methodsmentioning
confidence: 99%
“…7 Conversely, it has been demonstrated that magnetic resonance (MR) imaging (MRI) with subsequent MRI/ transrectal ultrasound (MRI/TRUS) fusion-guided biopsy of the prostate has a high level of sensitivity and a high positive predictive value for identifying CaP with a correlation to clinical significance. [8][9][10] In the current study, for the first time to our knowledge, we compared the performance of the PCPTHG and multiparametric-MRI (MP-MRI) in identifying men at risk of high-grade or clinically significant CaP for prostate biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…but can also be used to evaluate tumor volume [31,32]. The diagnostic accuracy of the morphological MRI examination can be increased by MR spectroscopy from 52 % to 75 % [10].…”
Section: Dynamic Contrast-enhanced (Dce) Mrimentioning
confidence: 99%